Public communication in the aftermath of an aviation disaster : a comparison of SilkAir, SIA and a foreign airline, Swissair - Ang, Yee Ling (2008)
This research aims to determine whether SIA had improved in the communication aspect of crisis management over SilkAir after the air crashes and their weaknesses when compared to a foreign airline, Swissair.